Learning from pandemic responses: Informing a resilient and equitable health system recovery in Thailand - Tangcharoensathien, Viroj; Vandelaer, Jos; Brown, Richard; Suphanchaimat, Rapeepong; Boonsuk, Phiangjai; Patcharanarumol, Walaiporn (Frontiers in Public Health, 2023)
This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict’. The third quarter of 2022 saw COVID-19 cases and deaths in Thailand reduced significantly, and high levels of COVID-19 vaccine coverage. COVID-19 was declared an “endemic” disease, and economic activities resumed. This paper reviews pre-pandemic health systems capacity and identifies pandemic response strengths, weaknesses and lessons that guided resilient and equitable health system recovery. Robust health systems and adaptive strategies drive an effective pandemic response. To support health system recovery Thailand should (1) minimize vulnerability and extend universal health coverage to include migrant workers and dependents; (2) sustain provincial primary healthcare (PHC) capacity and strengthen PHC in greater Bangkok; (3) leverage information technology for telemedicine and teleconsultation; (4) enhance and extend case and event-based surveillance of notifiable diseases, and for public health threats, including pathogens with pandemic potential in wildlife and domesticated animals. This requires policy and financial commitment across successive governments, adequate numbers of committed and competent health workforce at all levels supported by over a million village health volunteers, strong social capital and community resilience. A strengthened global health architecture and international collaboration also have critical roles in establishing local capacities to develop and manufacture pandemic response products through transfer of technology and know-how. Countries should engage in the ongoing Inter-government Negotiating Body to ensure a legally binding instrument to safeguard the world from catastrophic impacts of future pandemics.